IMPLEMENTASI METODE TAHSIN DALAM MENINGKATKAN KUALITAS BACAAN AL-QUR’AN DI LEMBAGA GRIYA AL-QUR’AN SURABAYA UTARA - Din Muhammad Zakariya; Abdullah Djamal Al Amudy (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
The background study this done because the problem that happen today's in our society, especially for adult and old people who can’t read the Al-Qur’an properly and correctly, there are no institutions that give them opportunities for learning, and there is no method specifically build for adults and old age, all that both of method and institutions that circulates in our society is just for toddler and kids. In here the institution's own the Tahsin methodology that is customized for adults and old people.In this thesis there are three problem formulations, First, How Quality of Al-Qur'an Reading of students at Griya Al Qu'ran Institute, North Surabaya. Second, How is the Implementation of the Tahsin Method in Improving the Quality of Reading Al- Qur'an at Griya Al Qur'ran Institute, North Surabaya. Third, What are the Supporting and Inhibitor Factors Implementation Tahsin Method in Increasing Quality Reading Al-Qur'an in Institution Griya Al Qu'ran North SurabayaThis type of research is descriptive qualitative research that collects data through interviews from parties directly related to learning and teaching activities at Griya Al-Qur'an, from students, teachers, branch managers and curriculum manager, after all data is collected in further qualitative analysis And described in descriptive form.The results of the study concluded that the Tahsin method was used by Griya The Qur'an is a method that is already understood and no students are experience difficulties in studying it, while the thing that supports it is the location which is strategically owned by Griya Al-Qur'an North Surabaya and the study hours are flexible, while the inhibiting factor is the ability of students in understand explanation Teacher And also a factor activity student at outside Griya Al-Qur'an